Hydrolyzation of duck meat protein using Bacillus cereus TD5B protease, pepsin, trypsin and their potency as an angiotensin converting enzyme inhibitor - Winarti, A.; Rahmawati, F.; Fitriyanto, N. A.; Jamhari, J.; Erwanto, Y. (Diponegoro University, 2019)
This study was aimed to explore their potency of protein-bioactive of native ducks-meat after enzymatic hydrolysis by Bacillus-cereus TD5B-protease, Pepsin, and Trypsin as an angiotensin-converting enzyme (ACE) inhibitor. The samples: ducks-meats from 10 months age of male Mojosari and Magelang-Duck. The experiments: individually hydrolysis of meat-protein using protease-enzyme (0.1 % w/w) from Bacillus-cereus TD5B, Pepsin, or Trypsin. The observed parameters: protein concentration, protein molecular weight, ACE-inhibitor activity, and IC-value (IC50). Data of protein concentration were statistically analyzed using T-Test, while data of SDS-PAGE and ACE-inhibiting activity were analyzed descriptively. The results showed that soluble protein concentration increased due to the hydrolysis process, from 0.826±0.108 mg/mL to 1.050±0.197 mg/mL (Microbial-protease), 2.122±0.141 mg/mL (pepsin), 1.641±0.071 mg/mL (trypsin) for Mojosari-duck and 0.642±0.038 mg/mL to 1.171±0.534 mg/mL(Microbial-protease), 2.100±0.376 mg/mL(pepsin), 1.725±0.092 mg/mL(trypsin) for Magelang-duck. The SDS-PAGE pattern showed that there was a decrease of molecular weight of duck-meats due to the hydrolysis process, from the range of 196.53-43.88 kDa to the range of 71.35-10.12 kDa. Duck-meat protein hydrolysate had ACE-inhibiting activity 71.7%(Mojosari-Microbial-Protease) IC50 54μg/mL, 57%(Mojosari-Pepsin) IC50 151μg/mL, 75.8%(Mojosari-Trypsin) IC50 51μg/mL and 52.8%(Magelang-Microbial-Protease) IC50 83μg/mL, 78,5%(Magelang-Pepsin) IC50 85μg/mL, 83.9%(Magelang-Trypsin) IC50 22μg/mL. In conclusion, hydrolysate of Magelang duck-meat used Trypsin had better potency as an ACE-inhibitor.